Begrebet arbejde i de danske senmiddelalderlige kalkmalerier - Nørregård, Martin Bo (Hikuin, 2007)
The Concept of Labour in the Danish Medieval Wall Paintings By Martin Bo Nørregaard This article examines the perception of manual labour through the late medieval wall paintings preserved in the Danish churches. The written sources concerning the attitude towards manual labour in medieval Denmark are very scarce, and most likely only reflect how manual labour was seen by the elite. Almost nothing is known about how the major part of the population perceived the manual labour which was their daily lot – neither in Denmark nor in the rest of Europe. In view of the lack of written sources it seems logical to try to use the richness of medieval wall paintings that are preserved in the Danish churches to shed some light on the concept of labour in Denmark. It is even possible that the wall paintings to some degree reflect the view of those who laboured manually, as a number of things indicate that the they began to visit the churches more often and in greater numbers as well as to influence the design of the churches in the later part of the Danish Middle Ages. There are many different depictions of manual labour on the walls and vaults of the Danish churches, but the most common is Adam and Eves Life on Earth. From late-medieval times this motive is preserved in 31 churches. Through a quantitative analysis it is examined whether the depiction of Adam and Eves Life on Earth differs from the text of the Bible or not, and if some interesting patterns can be found. The Bible only mentions that Adam has to work the cursed earth in the sweat of his face, and it is therefore striking that Adam in almost half of the churches is ploughing. The plough being the biggest and most valuable tool the peasants possessed and therefore implying a certain amount of wealth, indicating a positive view on manual labour. The clothes of Adam and Eves point in the same direction, in almost all of the 31 churches their clothes are depicted as average on a level between the clothes of the two extremes in The Prayer of the Rich and the Poor. It is however difficult to reach any definite conclusion on the perception of manual labour in the Danish wall paintings. The preserved wall paintings are too few in numbers and too little is known about the situation in which they were created. Who ordered and paid for them? How large a degree of freedom did the painter posses and how did he perceive himself, did he think himself as belonging to those who did manual labour and in which way did it affect his view on the peasantry which he depicted in Adam and Eves Life on Earth? Can his way of depicting be at all seen as more than an aesthetical choice?